Spatial and temporal evolution trends of groundwater drought and its correlation with meteorological drought in Guizhou province - Aili Wang; Yuanxiao Xing; Shunsheng Wang; Donglin Wang; Cundong Xu (Agricultural Water Management)
Groundwater constitutes a vital water resource in karst regions, where conventional surface-based drought indicators frequently fail to accurately capture groundwater deficits. However, the applicability of GRACE satellite data for monitoring groundwater drought in these complex environments remains uncertain. To address this limitation, this study developed a Groundwater Drought Index (GDI) utilizing GRACE gravity satellite data and applied it to Guizhou Province in Southwest China, a representative karst region. Sen’s slope estimator, the Mann-Kendall test, and Pearson correlation analysis were employed to assess the spatiotemporal trends of groundwater drought and its relationship with meteorological drought. The results indicate that: (1) GRACE-derived total water storage anomalies (TWSA) are significantly correlated with GLDAS data and exhibit consistent seasonal fluctuations; (2) groundwater storage anomalies (GWSA) demonstrate a significant increasing trend of 0.55 cm/year from 2003 to 2022, with the most pronounced seasonal declines occurring in winter and spring; (3) the GDI identified 12 groundwater drought events, primarily concentrated between 2003 and 2011, characterized by longer duration and greater intensity in the northern region; and (4) groundwater drought responds to meteorological drought with lags mainly ranging from 10 to 24 months. These findings confirm the effectiveness of GRACE data for groundwater drought monitoring in karst regions and provide a valuable reference for water resource management and early warning systems.